تأثير نقاط الضبط على الطريقة المباشرة لتصحيح التشوهات الهندسية في الصور القريبة - الخليل, عمر (Latakia University Journal -Engineering Sciences Series, 2016)
تنشأ التشوهات الهندسية في الصور القريبة من عدة مصادر وهي تؤثر على كامل الصورة بشكل مشترك. وهذه التشوهات تؤثر على النوعية الهندسية للبيانات المكانية المقتطعة من الصورة ولذلك لابد من تصحيحها قبل ذلك بعملية تسمى تقويم الصورة. يتوفر أسلوبان لتقويم الصور القريبة وهما الأسلوب غير المباشر والأسلوب المباشر Non-parametric approach وهو لا يتطلب معرفة معاملات آلة التصوير المستخدمة. تعتبر نقاط الضبط Control points والتحويلات الهندسية مكونين أساسيين في الأسلوب المباشر للتقويم.عادة ما تتواجد تشوهات التكور Barrel والمنظورية Perspective في الصور القريبة. في هذا البحث سنقوم بدراسة تأثير نمط توزيع نقاط الضبط ودرجة التحويل الهندسي على تصحيح الصورة من هذه التشوهات. تم إجراء الاختبار باستخدام صورة قريبة لواجهة أثرية مع تعريضها للتشوهات السابقة بالمحاكاة. الهدف هو التحري عن تأثير توزيعات نقاط الضبط وعن فعالية التحويلات العامة (الخطية) والمحلية (اللاخطية) المستخدمة في تقويم الصور القريبة. لقد تمت البرهنة على أن نقاط الضبط المتواجدة في مناطق مختلفة من الصورة تملك نسب تشوه مختلفة وأن نقاط الضبط الموزعة في مركز الصورة تعاني تشوهاً أقل وأن التحويلات المحلية تعطي نتائج أفضل عند تقويم الصور ذات التشوهات المعقّدة.There are many sources that cause the emergence of geometric deformations in close range images. These deformations are accumulated and not present singly in the image. Therefore, it is necessary to rectify (correct) the image before extracting geometric or semantic data from it.Two methods are available to rectify the close range images. These ones are the parametric and the non-parametric methods. Non-parametric approach does not require knowledge of the parameters of the used camera. Control points and geometric transformations are considered as the two main components in the non-parametric approach.Usually, barrel and perspective deformations are present in close range images. In this paper, we will study the impact of the distribution of control points and the degree of geometric transformation on the correction of the image of these deformations. The test was performed using a close range image of a historical façade. This image was exposed to previous deformations by simulation. The goal is to investigate the effect of the distribution of control points and on the effectiveness of global (linear) and local transformations used to rectify the close range images. It has been demonstrated that the control points located in different parts of the image have different deformation rates, the control points distributed in the center of the image suffers less deformations, and local transformations give the best results when rectifying images with complex deformations